Forensic Examination of Inks Extracted from Printed Documents Using Fourier Transform Infrared Spectroscopy - Ameh, Paul Ocheje; Ozovehe, Musa Suud (Edelweiss Applied Science and Technology, 2018)
Yellow, cyan, magenta and black inks were extracted from documents printed using two common brands of printing cartridge in Nigerian market and analyzed to identify / compare the functional groups present using Fourier Transform Infra-red Spectroscopy (FTIR). The FTIR spectra obtained were found to show highly characteristic absorption bands depending on the composition of the printer inks. Also, the results indicated the presence of triarylmethane dyes, epoxy resins, alkyd resin and esters in all the inks as they are peaks assigned to the vibration of aliphatic ester, asymmetrical and symmetrical stretching. The pure ink and its extract from the same band were also found to exhibit similar FTIR spectra while inks extract from different brands exhibits marked difference in absorption bands. This research can provide valuable information if an admitted sample is provided for comparing with the suspect printed document.